The Role of Sildenafil in Treating Brain Injuries in Adults and Neonates - Xiong, Ying; Wintermark, Pia (Frontiers in Cellular Neuroscience, 2022)
Sildenafil is a recognized treatment for patients suffering from erectile dysfunction and pulmonary hypertension. However, new evidence suggests that it may have a neuroprotective and a neurorestorative role in the central nervous system of both adults and neonates. Phosphodiesterase type 5—the target of sildenafil—is distributed in many cells throughout the body, including neurons and glial cells. This study is a comprehensive review of the demonstrated effects of sildenafil on the brain with respect to its function, extent of injury, neurons, neuroinflammation, myelination, and cerebral vessels.